2005
DOI: 10.1207/s15327736me1801_3
|View full text |Cite
|
Sign up to set email alerts
|

Local Advertising Decision Makers' Perceptions of Media Effectiveness and Substitutability

Abstract: In this article, we report the results of a survey designed to answer 6 questions on perceived media effectiveness and substitutability within the context of local advertising. Results from questionnaires completed by 130 local advertising decision makers reveal that (a) daily newspapers and radio are perceived as the most effective media for local advertising; (b) media interchangeability in local advertising is limited to a particular set of media options, namely, daily newspapers and radio; and (c) patterns… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 15 publications
0
8
0
Order By: Relevance
“…Not surprisingly, there is evidence in the literature that suggests that the main effect of national advertising is positive (e.g., Anderson and Simester 2004; Dekimpe and Hanssens 1999; Hirschey 1982). Likewise, although evidence is less rampant, extant literature has also indicated that regional advertising boosts firm performance (e.g., Nowak, Cameron, and Krugman 1993; Reid et al 2005). Finally, there is also sufficient evidence that online advertising positively influences firm performance (e.g., Agarwal, Hosanagar, and Smith 2011; Agarwal, Athey, and Yang 2009).…”
Section: Conceptual Backgroundmentioning
confidence: 99%
“…Not surprisingly, there is evidence in the literature that suggests that the main effect of national advertising is positive (e.g., Anderson and Simester 2004; Dekimpe and Hanssens 1999; Hirschey 1982). Likewise, although evidence is less rampant, extant literature has also indicated that regional advertising boosts firm performance (e.g., Nowak, Cameron, and Krugman 1993; Reid et al 2005). Finally, there is also sufficient evidence that online advertising positively influences firm performance (e.g., Agarwal, Hosanagar, and Smith 2011; Agarwal, Athey, and Yang 2009).…”
Section: Conceptual Backgroundmentioning
confidence: 99%
“…Therefore, we assumed that magazines are a cost-effective medium that can be used to plan marketing strategies. Reid et al (2005) examined local decision makers' perceptions of media effectiveness and substitutability and found that, compared to other media, daily newspapers and the radio are most effective locally. They also found that media compatibility is restricted to particular types of media such as newspapers and radio.…”
Section: Introductionmentioning
confidence: 99%
“…Media content is highly dependent on the cultural context. For instance, only a fraction of news content can be reused in other markets since most news broadcasts are relevant only in a certain market and recipients, as well as advertisers, are interested in local, regional or national content (Reid et al 2005;Aldridge 2003). Entertainment content generally travels more easily, although cultural and linguistic borders exist as well.…”
Section: Internationalizationmentioning
confidence: 99%